Review of Grotiusomyia Girault (Chalcidoidea: Eulophidae), an exclusively New World genus, including 17 new species - Hansson, Christer (Zootaxa, 2023)
The genus Grotiusomyia Girault is reviewed based mainly on material from Costa Rica. Grotiusomyia is an exclusively New World genus now represented by 19 species, of which 17 are new species described here: G. albiclava, G. annesmithae, G. azofeifai, G. flavicoxa, G. flavimacula, G. guanacastensis, G. hansoni, G. jimenezi, G. lascrucensis, G. leucaena, G. nicoyae, G. noyesi, G. phalaros, G. pilosa, G. reticulata, G. rubii, G. septentrionalis. The two previously described species are G. nigricans (Howard) and G. flavicornis Girault. An identification key for the species is included. Two of the species, G. flavicornis and G. septentrionalis are found in North America (USA and Canada respectively), while the remaining species are from Central America and the West Indies. The biology is known for three of the species, acting as ectoparasitoids on caterpillars of various Lepidoptera groups.